Pair distribution function analysis applied to decahedral gold nanoparticles. (16th October 2017) - Nakotte, H; Silkwood, C; Page, K; Wang, H-W; Olds, D; Kiefer, B; Manna, S; Karpov, D; Fohtung, E; Fullerton, E E
Abstract: The five-fold symmetry of face-centered cubic (fcc) derived nanoparticles is inconsistent with the translational symmetry of a Bravais lattice and generally explained by multiple twinning of a tetrahedral subunit about a (joint) symmetry axis, with or without structural modification to the fcc motif. Unlike in bulk materials, five-fold twinning in cubic nanoparticles is common and strongly affects their structural, chemical, and electronic properties. To test and verify theoretical approaches, it is therefore pertinent that the local structural features of such materials can be fully characterized. The small size of nanoparticles severely limits the application of traditional analysis techniques, such as Bragg diffraction. A complete description of the atomic arrangement in nanoparticles therefore requires a departure from the concept of translational symmetry, and prevents fully evaluating all the structural features experimentally. We describe how recent advances in instrumentation, together with the increasing power of computing, are shaping the development of alternative analysis methods of scattering data for nanostructures. We present the application of Debye scattering and pair distribution function (PDF) analysis towards modeling of the total scattering data for the example of decahedral gold nanoparticles. PDF measurements provide a statistical description of the pair correlations of atoms within a material, allowing one to evaluate the probability of finding two atoms within a given distance. We explored the sensitivity of existing synchrotron x-ray PDF instruments for distinguishing four different simple models for our gold nanoparticles: a multiply twinned fcc decahedron with either a single gap or multiple distributed gaps, a relaxed body-centered orthorhombic (bco) decahedron, and a hybrid decahedron. The data simulations of the models were then compared with experimental data from synchrotron x-ray total scattering. We present our experimentally derived atomistic models of the gold nanoparticles, with surprising results and a perspective on remaining challenges. Our findings provide evidence for the suitability of PDF analysis in the characterization of other nanosized particles that may have commercial applications.